ЦИТАТЫ НА ВСЯКИЙ СЛУЧАЙ: ЦЫГАНСКИЕ СЛОВА В СЛОВАРЕ КРИМИНАЛЬНОГО ЖАРГОНА (Filološke studije, 2019)
Last decades in Russia are signified with publication of many new jargon dictionaries. Their lexical materials look fresh and partly unprecedented. Nevertheless their sources are very obscure. Romani words listed in these dictionaries are unique. As I have already demonstrated in the preceding papers, they were mostly taken immediately from an unrecognizable German dictionary. These plagiarized parcels, as L. Milyanenkov declared, create so called «international» jargon, unknown before and probably fantastic. In the mean time they are also included into Russian jargon, as can be seen in D. Baldaev’s dictionary. One can conclude that at least one decision is wrong. 1) An «international» word fezavo means ‘lame’. It is «German» misreading of a Romani word «vesavo ... lahm» (Wolf, 1956: p. 339), taken from: «Vesavo (Cripple, lame)» (Pott, 1845: vol. II, p. 85). I suppose it should be an alias of an Angloromani adjective (in North Hampshire) «Vasavo Bad» (vesava peras = Lame feet). A.F. Pott found this word in a book of 1830 by colonel J.S. Harriot. Hundred years after Pott’s book was carelessly quoted in a dictionary for German police officers. It was an odd idea that this word, which means ‘bad’ in Angloromani, could help to detect some bad guys in Germany. The first result comes 70 years later: two Russian jargon dictionaries plagiarize this word in a confused form. 2) Romani dialect in Spain can give illusory words as well as any: an «international» word xerami means ‘bracelet’. Cp.: «Cherami [864] Armband» (Wolf, 1956: p. 72). From: «Jerámi f. Bracelet. Manilla» (Pott, 1845: vol. II, p. 171; Borrow, 1843: vol. II, p. 62). I believe that this «manilla» should be read as ‘mantilla’, cp. the same word in different spelling forms: «Erajami, s. f. Dress of a friar. Habito de fraile»; «Jarami, s. f. Jacket. Chaqueta»; «Jesame, s. f. Waistcoat. Chupa» (Borrow, 1843: vol. II, p. 48–62). Thus, neither in Spain, nor in Germany the word jerami does not signify ‘bracelet’. 3) An «international» word tseppo ‘breast’ comes from the same Borrow’s book (Chepo) and means ‘bosom’, cp. Turkic djep, etc. ‘pocket, bag’. 4) A.J. Puchmayer described one Czech Romani dialect in 1821. Some words of this dialect have long and unusual lives in dictionaries. One of them: «international» word «Kariólo – meat». From: «Karialo m. das Fleisch» (Pott, 1845: vol. II, p. 118). It really means ‘hedgehog’. One can understand that Romani words traditionally compiled and spared in jargon dictionaries are hardly useful in any sense. Linguistically they are worthless, as plagiarized.